2007
DOI: 10.1080/10428190701321277
|View full text |Cite
|
Sign up to set email alerts
|

Clinical progression and outcome of patients with monoclonal B-cell lymphocytosis

Abstract: Monoclonal B-cell lymphocytosis (MBL) is a clonal lymphoproliferation with the immunophenotype of chronic lymphocytic leukemia (CLL) but a B-lymphocyte count of less than 5 x 10(9)/l and no lymphadenopathy, organomegaly, cytopenias or symptoms. We performed a retrospective analysis of patients with MBL (n = 46), Rai stage 0 CLL (n = 112) and Rai stage > or =1 CLL (n = 54). Median follow-up and range was 30 (0.1-120) months for MBL, 60 (0.1-309) months for stage 0 CLL and 54 (0.1-309) months for stage > or =1 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
2
33
0
3
Order By: Relevance
“…[3][4][5][6] Although a recent study suggested that CLL is almost always preceded by a period of MBL, it has been estimated that the rate of progression of clinical CLL-type MBL to CLL is only 1-2% per year. 4,5,8,13 Several studies have demonstrated that the B-cell count predicts progression to CLL/SLL, treatment-free survival, and overall survival as a continuous variable. 5,[9][10][11] While the likelihood of treatment in clinical MBL is lower than in Rai stage 0 CLL, it remains uncertain whether there is a clinically significant difference in survival between patients with clinical MBL and those with Rai stage 0 CLL with a relatively low MBC count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Although a recent study suggested that CLL is almost always preceded by a period of MBL, it has been estimated that the rate of progression of clinical CLL-type MBL to CLL is only 1-2% per year. 4,5,8,13 Several studies have demonstrated that the B-cell count predicts progression to CLL/SLL, treatment-free survival, and overall survival as a continuous variable. 5,[9][10][11] While the likelihood of treatment in clinical MBL is lower than in Rai stage 0 CLL, it remains uncertain whether there is a clinically significant difference in survival between patients with clinical MBL and those with Rai stage 0 CLL with a relatively low MBC count.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] While blood counts remain stable over time in the vast majority of patients with clinical MBL, progression to CLL occurs in a small proportion of patients at a rate that has been estimated to be approximately 1-2% per year. 4,5,13 The most important predictor of outcome in clinical MBL appears to be the B-cell count at diagnosis, with several studies demonstrating that the B-cell count predicts progression to CLL, treatment-free survival, and overall survival as a continuous variable. 5,[9][10][11] Currently, a PB MBC count of 5¥10 9 /L is the WHO criterion that differentiates MBL from CLL; however, there are differences in the literature regarding the optimal B-cell thresholds that best predict the risk of progression, treatment-free survival and overall survival, with these thresholds ranging from 1.2¥10 9 /L to 11¥10 9 /L.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] We did not have information about MBL in our registry study so we could not evaluate the general risk of MBL among relatives of CLL cases. However, the transformation rate from MBL to CLL requiring therapy is only about 1% per year 30,31 and has been shown to depend on the level of lymphocytosis seen at diagnosis. 31,32 These characteristics of CLL make it quite different from other common solid tumors where early detection of the tumor or precursor can affect survival.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…6,8,9,[14][15][16] In a recent study, Rawstron et al 6 reported the clinical outcome of a cohort of 185 CLL-type monoclonal B-cell lymphocytosis cases observed over a 6.7-year period. The B-cell count (< or ≥1.9¥10…”
Section: )mentioning
confidence: 99%